A clinically feasible short version of the 15-item geriatric depression scale extracted using item response theory in a sample of adults aged 85 years and older. (1st February 2022) - Johansson, Sanna; Lövheim, Hugo; Olofsson, Birgitta; Gustafson, Yngve; Niklasson, Johan
Abstract: Objectives: To extract the items most suitable for a short version of the 15-item Geriatric Depression Scale (GDS-15) in a sample of adults aged ≥ 85 years using item response theory (IRT). Method: This population-based cross-sectional study included 651 individuals aged ≥ 85 years from the Umeå 85+/GErontological Regional DAtabase (GERDA) study. Participants were either community dwelling (approximately 70%) or resided in institutional care (approximately 30%) in northern Sweden and western Finland in 2000–2002 and 2005–2007. The psychometric properties of GDS-15 items were investigated using an IRT-based approach to find items most closely corresponding to the GDS-15 cut off value of ≥5 points. Receiver operating characteristic curves were used to compare the performance of the proposed short version with that of previously proposed short GDS versions. Results: GDS-15 items 3, 8, 12, and 13 best differentiated respondents' levels of depressive symptoms corresponding to the GDS-15 cut off value of ≥5, regardless of age or sex, and thus comprise the proposed short version of the scale (GDS-4 GERDA). For the identification of individuals with depression (total GDS-15 score ≥ 5), the GDS-4 GERDA with a cut-off score of ≥2 had 92.9% sensitivity and 85.0% specificity. Conclusion: The GDS-4 GERDA could be used as an optimized short version of the GDS-15 to screen for depression among adults aged ≥ 85 years.